LEGALITY OF THERAPEUTIC CONTRACTS IN HANDLING HEALTH FROM THE LEGAL PERSPECTIVE OF AGREEMENTS AND HINDU LAW - Habibi Habibi; I Putu Pasek Bagiartha W (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
Health is a very important factor and has become a basic necessity for human life. When humans are sick and have to get certain medical actions we have to sign a contract which is called a Therapeutic contract. The purpose of this study was to determine the legality of the therapeutic contract in the perspective of Hindu law and contract law. The approach method in this research uses normative legal research methods. The legality of a therapeutic contract, both from the perspective of treaty law and Hindu law, refers to the arrangements regarding the validity of the agreement and the conditions for binding the contract or pacta sunt servanda. In the agreement law, the provisions for the validity of the agreement are contained in the provisions of Article 1320 of the Civil Code and regarding the conditions for binding contracts are regulated in Article 1338 of the Civil Code. Whereas in Hindu law, the arrangements regarding the validity of the agreement and the conditions for binding the contract are regulated in Book VIII Manawa Dharmasastra, namely for the legal terms of the agreement in Book VIII Sloka 165 (agreement), Sloka 163 (skill), Sloka 143 (achievement), and Sloka 164 (causa kosher); The conditions for binding contracts (pacta sunt servanda) are stipulated in Book VIII Sloka 46. As well as being sourced from the Civil Code and Manawa Dharmasastra, therapeutic contracts whose object is inspanning verbintenis (medical action based on effort, not results achieved) are also subject to the provisions of national law as stated in the Minister of Health Regulation Number 290 of 2008 concerning Approval of Medical Action.